Adsorption and Leaching of Deltamethrin Pesticide in Alluvial Soil Under Laboratory and Field Conditions - M. Ashraf Bajeer, Zahid Hussain Shar, Nizamuddin Solangi, Sorath Solangi, M. A. Mallah, M. Kashif Channa, S. T. H. Sherazi, (Pakistan Journal of Medical & Health Sciences, 2022)
This study was carried out to assess the adsorption and leaching activities of deltamethrin pesticide in soil and water. Experiments in the lab and in the field were used to better understand these processes and the factors that influence them. Sections of the adsorption experiment were separated into kinetic and steady-state. Pseudo-first and second-order models were used to evaluate the kinetic data. Deltamethrin kinetic adsorption on soil was shown to be pseudo second order, with a rate constant of 4.625 mg/g/h. Using the Langmuir and Freundlich isotherms, it was determined that Freundlich's isotherm was well-observed, with adsorption capacities of 0.164-0.861 mole per gramme, based on the equilibrium data. In the lab, leaching experiments were carried out in 30-cm-long plastic columns. After adsorption, 500 ml of water was used to elute a known amount of deltamethrin insecticide from the column. It was discovered that the deltamethrin concentration fell from 0.405 ng/l in the first portion of the water to 0.0601 ng/l in the last portion of the water and 2.584 ng/l in the first section of column soil to 0.278 ng/l in the third section of column soil. Deltamethrin's leaching capability was tested in the field to a depth of 30 cm, and its concentration declined as soil depth increased. In the first piece of soil, it was 10.518 ng/l, and in the third, it was 0.354 ng/l. It was discovered in this investigation that deltamethrin insecticide leached to 30 cm depth because to minimal organic matter, sandy texture and basic pH.